Numerical investigation of hydrogen charging performance for a combination reactor with embedded metal hydride and coolant tubes. (1st June 2015) - Bhouri, Maha; Bürger, Inga; Linder, Marc
Abstract: A two-dimensional model investigating the hydrogen charging process in a combination reactor filled with both LaNi4.3 Al0.4 Mn0.3 and 2LiNH2 -1.1MgH2 -0.1LiBH4 -3 wt.%ZrCoH3 materials has been developed. The selected configuration is a cylindrical reactor of 32 cm of diameter where the MeH is filled in annular tubes separated from the complex hydride bed by a gas permeable layer. The diffusion of hydrogen towards the two storage media is ensured by filters embedded in the middle of the MeH tubes whereas the coolant tubes are placed in the centre of their triangular arrangement. Simulation results have shown that the charging process depends on the MeH reaction heat required for the initiation of the CxH reaction as well as the heat management once the complex hydride starts to store hydrogen. High hydrogen storage rates and short refueling times can be obtained by increasing the number of MeH and coolant tubes and ensuring an efficient heat removal at the peripheral area of the CxH media. A refueling time of 3 min is achieved for an optimum configuration of 49 MeH tubes and 96 coolant tubes while increasing the thermal conductivity of the CxH media to 3.5 W/(m K). Such a result could make the identified optimum configuration as a suitable hydrogen storage system for fuel cell forklift trucks since it meets the requirements of this application in terms of weight and size. Highlights: H2 charging performance of a combination reactor with embedded coolant tubes. Effect of MeH tubular tubes thickness and number. Effect of coolant tubes number and CxH thermal conductivity. Optimum configuration with 3 min charging time has been identified. Optimum configuration is suitable for fuel cell forklift applications.